Microbiome Structure of a Wild Drosophila Community along Tropical Elevational Gradients and Comparison to Laboratory Lines - Brown, Joel J; Jandová, Anna; Jeffs, Christopher T; Higgie, Megan; Nováková, Eva; Lewis, Owen T; Hrček, Jan (Applied and environmental microbiology, 2023)
Variation along environmental gradients in host-associated microbial communities is not well understood compared to free-living microbial communities. Because elevational gradients may serve as natural proxies for climate change, understanding patterns along these gradients can inform our understanding of the threats hosts and their symbiotic microbes face in a warming world. In this study, we analyzed bacterial microbiomes from pupae and adults of four Drosophila species native to Australian tropical rainforests. We sampled wild individuals at high and low elevations along two mountain gradients to determine natural diversity patterns. Further, we sampled laboratory-reared individuals from isofemale lines established from the same localities to see if any natural patterns are retained in the lab. In both environments, we controlled for diet to help elucidate other deterministic patterns of microbiome composition. We found small but significant differences in Drosophila bacterial community composition across elevation, with some notable taxonomic differences between different Drosophila species and sites. Further, we found that field-collected fly pupae had significantly richer microbiomes than laboratory-reared pupae. We also found similar microbiome composition in both types of provided diet, suggesting that the significant differences found among Drosophila microbiomes are the products of surrounding environments with different bacterial species pools, possibly bound to elevational differences in temperature. Our results suggest that comparative studies between lab and field specimens help reveal the true variability in microbiome communities that can exist within a single species. IMPORTANCE Bacteria form microbial communities inside most higher-level organisms, but we know little about how the microbiome varies along environmental gradients and between natural host populations and laboratory colonies. To explore such effects on insect-associated microbiomes, we studied the gut microbiome in four Drosophila species over two mountain gradients in tropical Australia. We also compared these data to individuals kept in the laboratory to understand how different settings changed microbiome communities. We found that field-sampled individuals had significantly higher microbiome diversity than those from the lab. In wild Drosophila populations, elevation explains a small but significant amount of the variation in their microbial communities. Our study highlights the importance of environmental bacterial sources for Drosophila microbiome composition across elevational gradients and shows how comparative studies help reveal the true flexibility in microbiome communities that can exist within a species.
Keywords: mikrobiota; Drosophila; metabarcoding; Gastrointestinal Microbiome; ecology; střevní mikroflóra; Bacteria; Animals; field and laboratory; Microbiota; symbiosis; bacteria; microbiome; Austrálie; zvířata; Australia; elevation gradient; community